Corporate Cash Holdings: An Empirical Investigation of Indian Companies. Issue 4 (August 2019) - Arora, Ravinder Kumar
Abstract: The article examines the pattern of cash holdings of 266 Indian companies comprised in the S&P BSE 500 index for the period 2005–2015 to understand the factors that influence the level of cash balances, to estimate the amount of excess cash held by these companies and to analyse how these companies spend their excess cash. The sample companies hold approximately 12 per cent of their total assets as cash in 2015. The pattern of cash holdings of the sample companies is supported by the static trade-off and the financing hierarchy model. Consistent with earlier evidence, firms with large cash balances have strong growth opportunities, larger cash flows, higher cash flow volatility, higher leverage, higher level of promoter holding and belong to the government-owned sector. Companies that have more liquid assets other than cash have more tangible assets and pay more to their shareholders hold lower cash balances. However, contrary to earlier evidence, size of the firm is not related to the amount of cash holding. Further, firms with large cash balances have higher leverage. The study does not find association of cash holding with many other variables found to have association with cash holding in developed markets. A large number of the firms in the sample hold cash in excess of what is predicted on the basis of firm's characteristics. These companies manage their cash balances in a manner that is not consistent with maximization of shareholders' wealth.